O poznańskiej (i nie tylko) pedagogice społecznej - Matysiak-Błaszczyk, Agata; Włodarczyk, Ewa; Modrzewski, Jerzy (Wydawnictwo Naukowe UAM, 2016)
Social pedagogy in Poland already has a history of over a hundred years, with its roots in the positivist and socialist reflection of the socio-philosophical turn of the 20th century. Helena Radlinska is rightly credited with its problematization, theoretical and academic institutionalization; she was also the organizer and promoter of the Lodz and Warsaw scientific community. In the second half of the twentieth century other scientific communities were formed and continued some of her practice according to the paradigm proposed by Radlinska, as a praxeological science. These are teams of educators in Katowice, Torun, Bydgoszcz, Olsztyn, Szczecin, Opole, Bialystok, etc., initiating its presence in the rapidly developing centers of academic science and teaching. Against this background, the authors of this article reveal the genesis, original characteristics, development, achievements, and prospects of Poznan-based social pedagogy at the turn of the 21st century.
On Social Pedagogy in Poznan (and Beyond)
Keywords: social pedagogy; environment; sociology of education; educational sociology